An Investigation on Characteristics of GaN Based MOSFETs and Their Driving Circuits - , C. T. Ma; , Z. H. Gu (Archives of Current Research International, 2016)
Gallium nitride (GaN) based semiconductor devices are expected to play an important role in developing the next-generation power converters. With some intrinsic features, e.g., low switching power loss and high breakdown voltage, GaN MOSFETs can be used to realize high power density and better efficiency power converters with ultra-high switching frequencies. This paper firstly reviews characteristics of GaN based high electron-mobility transistors, some selected published papers and technical reports regarding applications of GaN MOSFETs in various power electronic systems and key issues regarding driving requirements of GaN MOSFETs followed by introducing a number of physical considerations in designing driving circuits and the related ICs. It follows that two practical driving circuits are designed on a given output voltage parameters in this paper. To verify the feasibility and effectiveness of the proposed driving schemes a 300 W synchronous buck converter with the proposed GaN gate drivers is constructed and tested. Some measured results are presented with brief discussions.